EFL Learners’ Reading Comprehension Level: What Do They Portray? - Nyimas Triyana Safitri; Melati Melati (Scope : Journal of English Language Teaching, 2023)
Levelling reading comprehension may help students learning and teacher course designing. This study attempts to portray the level of EFL reading comprehension in a public university in Jambi, Indonesia. The participants were 78 EFL learners who were registered in the academic year 2020-2021. The data were collected through administering a set of adapted reading test and calculated based on the indicator of the scoring system and criteria. These data were classified into each level of reading comprehension which is described in the form of percentage and presented through diagram and chart. The major findings of this study reveal that. 1) there were 77 or (99%) participants can complete most of the literal test items and they just achieved literal level of comprehension of reading skill. 2) there were 24 or (31%) participants were able to answer all inferential test items successfully and they just reach inferential level of reading comprehension. 3) there were 19 or (24%) participants can give their answer critically and they just obtained a critical level of reading comprehension. It is interpreted that numerous students were still in the position of the literal level which is regarded as a very low or basic level of reading comprehension. So, it is strongly recommended that EFL learners at Universitas Jambi require an intensive practice of reading to achieve a highest level of reading comprehension.